Legacy and novel brominated flame retardants in animal-derived foods from China Total Diet Study (CTDS): Temporal trends, evidence of substitution, and dietary exposure assessment - Zhao, Xuezhen; Lyu, Bing; Zhang, Lei; Li, Jingguang; Zhao, Yunfeng; Wu, Yongning; Shi, Zhixiong (Journal of hazardous materials, 2023)
Based on the 6th China Total Diet Study (CTDS) conducted in 2016–2019, the occurrence of both legacy and novel brominated flame retardants (BFRs) was measured in animal-derived foods collected across China. Most BFRs could be frequently detected in food samples, indicating their ubiquity in the environment. Decabromodiphenyl ethane (DBDPE), a typical novel BFR, presented the highest contamination level, whereas legacy BFRs, including decabrominated diphenyl ether (BDE-209), tetrabromobisphenol A (TBBPA), and hexabromocyclododecane (HBCDD), still presented high detection frequencies and relatively abundant proportions in total BFRs. Compared with previous CTDSs conducted from 2007 to 2011, the levels and estimated dietary intakes (EDIs) of most BFRs showed a significant downtrend, which suggested that flame retardant consumption in China has transferred from legacy BFRs to novel BFRs (mainly DBDPE) and from BFRs to other kinds of flame retardants. Based on probabilistic estimation, the median EDIs of mainly used BFRs for the Chinese population ranged from 41.0 to 1.67 × 103 pg/kg bw/day, and meat consumption was the primary source in dietary BFR intake. By conducting the margin of exposure (MOE) approach or comparing with the reference dose (RfD), it can be concluded that daily dietary intakes of BFRs were still unable to cause significant health risks to the general population in China. [Display omitted] •Both legacy and novel BFRs were measured in food composites collected across China.•DBDPE was the predominant BFR while legacy BFRs can still be frequently detected.•Levels and EDIs of most BFRs showed significant downtrend in the past years.•FR consumption in China has shifted from legacy BFRs to novel BFRs and other FR.•Dietary BFR intakes pose no significant health risks to general Chinese population.